Experimental and numerical investigation on effect of fluidization degree and temperature on bed agglomeration during bioslurry fast pyrolysis in a fluidized bed - Wenran Gao; Haoran Chen; Yi Liao; Yansheng Wu; Haonan Zhu; Hong Zhang; Jinping Weng; Xin Guo; Xun Hu; Xiongchao Lin; Karnowo; Shu Zhang (Fuel Processing Technology)
Bioslurry utilized in fluidized beds may occur bed agglomeration, and understanding the formation of bed agglomeration is significant for bioslurry efficient utilization. This study investigated the effects of fluidization degree and temperature on bed agglomeration during fast pyrolysis of bioslurry by numerical simulation and experiments. The findings indicated when the flow rate of fluidizing gas increased from 1.0 to 3.0 L/min, the agglomeration yield rose from 31.16 % to 48.08 %. Combined with the numerical simulation, it was proved that 2.0 L/min was the optimum flow rate for effective fluidization. Below it, fluidization could not be achieved and some sand particles were not contact with fuel. Above it, local agglomerations were caused by excessive gas flow. Research on the correlation between bed agglomeration and tar/char revealed that bed agglomeration was primarily governed by fluidization efficiency, not by tar/coke. Furthermore, increasing pyrolysis temperature effectively reduced the agglomeration yield. As the temperature rose from 300 to 800 °C, the agglomeration yield decreased from 52.58 % to 9.84 %. However, when temperature > 600 °C, further increasing temperature had a limited effect on mitigating agglomeration. Additionally, there was a linear positive correlation between bed agglomeration due to tar/coke and tar/coke yield, with coke consistently playing a key role.